Crystal structure and magnetic behavior within a new molecular magnet containing [Ni(dmit)2]− monoanion. Issue 3 (4th March 2017) - Zhang, Hui; Liu, Shao-Xian; Yu, Shan-Shan
ABSTRACT: In this study, a new metal-dithiolene charge transfer salt with a formula of [3, 4-Cl, Cl-Bz-1-APy][Ni(dmit)2 ] (1 ; 3, 4-Cl, Cl-Bz-1-APy = 1-N-(3′, 4′-dichlorobenzyl)pyridinium, dmit = l, 3-dithiole-2-thione-4, 5-dithiolate) was synthesized and characterized. The crystal of1-Me2 CO belongs to triclinic space group P-1, the [Ni(dmit)2 ] − anions and 3, 4-Cl, Cl-Bz-1-APy + cations form mixed column stacks with alternating anionic (A) and cationic (C) in the …ACAC… fashion, along the crystallographic a-axis direction. The [Ni(dmit)2 ] − anions formed a uniform one-dimensional chain via lateral-to-lateral S…S contacts. From the view of crystal structure, an uniform S = ½ Heisenberg linear chain model could be chosen for the fits of the temperature dependent magnetic susceptibilities of1, but the attempt on this fit is failed. The simple Curie-Weiss law was used for the fits of magnetic susceptibility of1 . The fitted Curie constant is larger than the spin-only value expected for an S = ½ system.